Intercession in the Maturidi School and its place in Kazakh Religious Literature - Syrym Shakizada; Askar Akimkhanov; Shamshadin Kerim; Zhalgas Sandybaev; Burkhanadin Abdilkhakim (Pharos Journal of Theology)
The concept of intercession is widely evidenced in Islamic texts. However, it was opposed by some significant Islamic sects and groups throughout history. This article is intended to provide evidence in favour of intercession and debunk the opposing position through analyzing the texts of Islamic scholars, alongside the Quran and hadiths. We also consider how the theological influence and prominence of this concept can be found in Kazakh Islam through an analysis of traditional Kazakh poetry. My task is to compare the concept of intercession as defined in Maturidi School teachings and traditional Kazakh religion, and therefore to demonstrate the spiritual importance that intercession has for Muslim believers.